External morphological anomalies of the amphibians of the Kharkiv region - Katrushenko, S. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
In Ukraine, amphibian anomalies have not been sufficiently studied. The most studied regions are Kyiv region and the steppe zone of Ukraine. In the Kharkiv region, studies of external anomalies of amphibians have not been conducted before. In 2016 we have begun to study this problem. The purpose of this study is to examine the variety of external anomalies of amphibians in the Kharkiv region. The material is sampling amphibians from the stock collections of the Museum of Nature of V.N.Karazin Kharkiv National University and sampling live amphibians from different localities of the Kharkiv region, explored in the period from 2016 to 2018. Anomalies were determined visually, according to the classification of V.L.Vershinin and O.D.Nekrasova. For each the amphibian species frequency of malformed animals Pas (the proportion of abnormal individuals from all individuals in the sample) and partial frequency of abnormalities Ap (the proportion of individuals in the sample having this anomaly) were determined. As a result 17 variants of morphological abnormalities were identified: brachydactyly, oligodactyly, ectromelia, polyphalangy, finger thickening, rotation, syndactyly, shizodactyly, ectrodactyly, skin web and growth on the foot, thaumelia, hemimelia, lack of a swimming membrane, anophthalmia, brachycephaly and pattern abnormal. The most widespread anomaly encountered in the surveyed amphibians is brachydactyly (accounting for almost half of the reported cases of morphological abnormalities). This limb anomaly is the least harmful, so individuals with such abnormalities are usually quite viable. Amphibian anomalies are evenly distributed among samples: the highest occurrence of individuals with anomalies was recorded in Lissotriton vulgaris, in other samplings of frog (except Bufotes viridis and Bombina bombina), the occurrence of individuals with anomalies did not exceed five percent. A new type of body color anomaly in this year's Bufotes viridis was also identified and described.